Diffusion-weighted MRI of fatty liver - Poyraz, Ahmet K.; Onur, Mehmet R.; Kocakoc, Ercan; Ogur, Erkin (Wiley-Blackwell, 2012)
Purpose: To investigate the effect of fat infiltration on the apparent diffusion coefficient (ADC) of liver, and assess the relationship between ADC and hepatic fat fraction (HFF). Materials and Methods: MRI scans of 120 consecutive patients were included in this retrospective study. Of these, 42 patients were included in the fatty liver group and 78 in the control group. ADC values were measured from a pair of diffusion-weighted (DW) images (b 0 mm(2)/s and 1000 mm(2)/s). HFFs were measured using T1W GRE dual-echo images. The difference between the ADCs of the two groups was assessed with the t-test. The relationship between HFF and ADC was determined using linear regression analysis and the Pearson correlation coefficient (r). Results: Mean HFFs were 0.85 +/- 2.86 and 13.67 +/- 8.62 in the control and fatty liver groups, respectively. The mean ADC of fatty liver group 1.20 +/- 0.22 x 10 (-3) mm (2)/s was significantly lower than that of the control group 1.32 6 0.23 x 10(-3) mm (2)/s (P = 0.02). Linear regression analysis revealed an inverse relationship between ADC and HFF (r = 0.39, P < 0.0001). Conclusion: ADC significantly decreases in patients with > 5% HFF, and ADC and HFF exhibit an inverse relationship. Key Words: MRI; diffusion-weighted; fatty liver; imaging; chemical shift J. Magn. Reson. Imaging 2012; 35: 1108-1111. (C) 2011 Wiley Periodicals, Inc.
Keywords: MRI; diffusion-weighted; fatty liver; imaging; chemical shift